Meeting the confused patient with confidence: perceived benefits of communication partner training in subacute TBI. (23rd February 2023) - Nielsen, Annesofie Ishøy; Jensen, Lise Randrup; Power, Emma
ABSTRACT: Objective: This study aims to explore health professionals' perceived benefits of implementing Communication Partner Training (CPT) using Supported Conversation for Adults with Aphasia (SCA™) in a subacute rehabilitation setting with patients in post-traumatic confusional state (PTCS) after TBI. Method: The study was conducted in a clinical setting using a pre-post questionnaire design to explore change. One hundred and four interdisciplinary clinicians attended CPT in the SCA™ method and subsequent implementation support. Participants completed a questionnaire with both quantitative and qualitative questions before and after the training and implementation period. Data were analyzed using descriptive and inferential statistics and qualitative content analysis. Results: Participants' perceived confidence and self-assessed ability to communicate with patients in PTCS significantly increased after CPT (p = 0.006). While participants still experienced communication challenges, they reported using CPT-related tools and strategies in their interactions. Participants found they could apply strategies to improve patients' comprehension of information and to confirm their understanding of patients' communication. However, using strategies to enhance patients' expressive abilities was perceived as more challenging. Conclusions: Training health professionals in CPT increase their confidence in managing communication with patients in PTCS. Further research is needed to evaluate the efficacy of CPT within a more rigorous research design.